(untitled) (Journal of history, 2020)
The article presents the results of archaeological excavations carried out in 2015 on the site of Aktobe. The excavations carried out on the cliff channel reservoir Aksu identified mass grave randomly scattered bones of the deceased of various age and gender. The results of the anthropo- logical examination of the remains of about 30 individuals from this burial found no traces of violent injuries on the bones and skulls. The results of anthropological research and analysis of archaeological artifacts led to the conclusion that it is connected with the burial of a religious ritual. The complex of ceramics were present in the burial makes it impos- sible to date the burial VIІ – IX century.